2019
DOI: 10.1002/wene.343
|View full text |Cite
|
Sign up to set email alerts
|

Participation of wind power producers in day‐ahead and balancing markets: An overview and a simulation‐based study

Abstract: At present, a harmonized pan-European electricity market (EM) is a close reality. While in day-ahead markets (DAMs) the harmonization is at an advanced stage, in balancing markets (BMs) still exist some challenging issues, notably the remuneration of imbalances: some countries have simple and clear methods, but others consider complex methods that are not appealing to the participation of variable renewable energy (VRE). The participation of VRE in BMs is technically feasible, although with some restrictions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…The results obtained demonstrate that NWP data availability determines the wind power forecast accuracy in the day-ahead market. In [6], by using a case study where wind parks are allowed to participate in the Portuguese tertiary reserve, the authors concluded that changing the market time unit from 1 h to 15 min reduces their imbalances about 10%. Thus, schedule updates as close as possible to real-time operation may strongly reduce the effect of forecast errors.…”
Section: The Role Of Wind Power Forecast In Day-ahead and Balancing Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained demonstrate that NWP data availability determines the wind power forecast accuracy in the day-ahead market. In [6], by using a case study where wind parks are allowed to participate in the Portuguese tertiary reserve, the authors concluded that changing the market time unit from 1 h to 15 min reduces their imbalances about 10%. Thus, schedule updates as close as possible to real-time operation may strongly reduce the effect of forecast errors.…”
Section: The Role Of Wind Power Forecast In Day-ahead and Balancing Mmentioning
confidence: 99%
“…These characteristics have a strong influence on the outcomes of energy markets, reducing market-clearing prices [3]. Accordingly, existing market designs should be analyzed to determine if they are still efficient to deal with high levels of VRE (see, e.g., [4][5][6]).…”
Section: Introductionmentioning
confidence: 99%
“…As noted earlier, the work published in [11] analysed the benefits of the participation of wind power producers in balancing markets at both economic and technical levels. We found that a reduction of the market time unit from 1 h to 15 min is beneficial to WPPs.…”
Section: Renewable Power Band Marketplacementioning
confidence: 99%
“…The simulations are performed with the help of the agent-based tool called MATREM (see [9,10]). Six key performance indicators (KPIs) are considered, namely the value of wind energy to the market, the global imbalances of the system, the imbalances and costs of WPPs and retailers, and the total cost of the system.The work presented here builds on our previous work in the areas of trading wind power in markets [11,12] and portfolio optimization of retailers [13]. Specifically, in [11], we investigated the benefits of the participation of WPPs in BMs at both economic and technical levels.…”
mentioning
confidence: 99%
“…However, the increasing levels of variable renewable energy, such as solar and wind power (WP), are raising some difficulties to energy markets (see, e.g., [1]). VRE depends on meteorological conditions, meaning that it is not dispatchable (but see [2]).…”
Section: Introductionmentioning
confidence: 99%